2021
DOI: 10.1002/psp.2461
|View full text |Cite
|
Sign up to set email alerts
|

Between stuckness and stillness: Why do young adults not undertake temporary mobility?

Abstract: Youth temporary mobility occurs for purposes such as volunteering, Erasmus exchanges and linguistic stays. Although it is increasingly common, a large proportion of young adults are not mobile. This study is based on a large-scale survey among young adults in Switzerland. It draws on the concept of motility to analyse the barriers to temporary mobility, where motility may be defined as a set of mobility resources that refer to three dimensions: access (e.g., financial means or time), skills (e.g., languages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…While the general SEU model advocates that a range of different goals and preferences are decisive, especially for young people, job-related reasons are a key determinant for spatial mobility (Haldimann et al 2021;Kalter 1997;Kaufmann et al 2018;Lemistre and Magrini 2011). The frame selection model (Esser 1990) states that individuals do not consider an arbitrary number of attributes when evaluating alternative actions, but focus their decisions on primary goals based on their situational dominance.…”
Section: Individual Occupational Orientationsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the general SEU model advocates that a range of different goals and preferences are decisive, especially for young people, job-related reasons are a key determinant for spatial mobility (Haldimann et al 2021;Kalter 1997;Kaufmann et al 2018;Lemistre and Magrini 2011). The frame selection model (Esser 1990) states that individuals do not consider an arbitrary number of attributes when evaluating alternative actions, but focus their decisions on primary goals based on their situational dominance.…”
Section: Individual Occupational Orientationsmentioning
confidence: 99%
“…Following life-cycle models widely used in migration research (Chen and Rosenthal 2008;Détang-Dessendre et al 2008;Wagner 1989) as well as the motility framework (Kaufmann et al 2004), it can be assumed that for young people in transition from school to VET, their mobility decisions are primarily guided by their occupational orientations. As studies have shown that mobility can be seen as an instrumental decision (Haldimann et al 2021;Kaufmann et al 2004;Schlimbach et al 2018;Waibel 2019), youths' occupational orientations constitute agentic push factors of becoming spatially mobile. Youths that aspire to occupations entailing a higher socio-economic status, such as IT specialists, industrial mechanics, or medical assistants, can expect higher benefits, e.g., in terms of monetary returns and social status, and thus have a higher motivation to achieve their aspired goals.…”
Section: Individual Occupational Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies we were able to trace are interview-based explorations among small numbers of research participants who could be identified as stayers (Hjälm, 2014 ; Stockdale et al, 2018 ; Thomassen, 2021 ). Several other studies—based on survey data—used information about the importance of fixed-category factors underlying desires or decisions to stay among specific categories of young adults (Haldimann et al, 2021 ; Hofstede et al, 2022 ; Hooijen et al, 2020 ; Rérat, 2016 ). These works have painted valuable pictures of people’s immobility experiences and uncovered some of the complexity of people’s decision-making processes.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of young adults pursue a temporary mobility experience, such as going abroad to learn a new language or taking a gap year (Haldimann, Heers, and Rérat 2021;King and Raghuram 2013;Smith, Rérat, and Sage 2014;Van Mol and Timmerman 2014;Zimmermann and Neyer 2013). Temporary mobility can be educational, professional, or cultural, but excludes holidays.…”
Section: Introductionmentioning
confidence: 99%